Improving English Communicative Competence at Tertiary Level of Education in Industrial Revolution 4.0 using Co-Trainers Program - Ratini Setyowati (Fakultas Komunikasi, Sastra, dan Bahasa, 2020)
English communicative competence is needed in this Industrial Revolution 4.0. Indonesia must prepare the high-skill categories needs for every aspect because it causes transformation. Therefore English Communicative Competence is one of the priorities at Tertiary Level of Education. The researchers designed English teaching model called Co-Trainers Program. The ojectives of the study were to explain the design of the Co-Trainers program and to describe the result of Co-Trainers program implementation at Tertiary Level of Education in order to improve English Communicative Competence. This research used descriptive qualitative method. This research describes and elaborates Co-Trainers program to improve English Communicative Competence. The research was done in two semesters. The populations of the research were Medical Records students in academic years 2018/2019 from they were at the first semester and at the second semester. There were 327 students. To get the data, the researchers used interview, questionnaires, and an oral test (pre-test and post-test). The result of the study is Co-Trainers program can improve students’ communicative competence, the average score of the students is getting better, their communicative competence was fair become good. Good means their communication is mostly fluent; a few unnatural pauses; fairly comprehensible. The Co-trainers program can be applied continously.